Importancia de la biotecnología aplicada para el mejoramiento genético del arroz (Oryza sativa L.) - Rivera Pazmiño, Nemias Jonathan (2024)
The cultivation of Oryza sativa rice is one of the most important foods in the world. At this time, the demand for rice is expected to increase by 40% by 2030. Demand that could only be satisfied by increasing the current cultivated area, or the colonization of new areas for the production of the crop. This, without incurring the different biotic and abiotic factors that in themselves reduce production. One way to increase production in the same crop area is biotechnology tools. These contribute from the 70s to the present. Genetic improvement produces new improved varieties that contribute to reducing the economic risks of the planted crop. Its benefit is reflected in the environment until it provides adaptability characteristics in soils and environments where the crop does not develop naturally. This bibliographic review work consists of indicating which are the main biotechnological tools, and which is the most used in the genetic improvement of plants. The main biotechnological tools used for the production of O. sativa rice plants are tissue culture, (organogenesis and embryogenesis), transgenic, and cisgenic. These last two propagation tools include genes from outside or within the plant species that contribute to better adaptability of the rice plant to the normal conditions to which they develop, making them tolerant and producing greater productivity.